Association between low back pain and quality of life in patients with rheumatoid arthritis according to patient-reported outcomes using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ): A cross-sectional study. Issue 5 (3rd September 2021) - Mochizuki, Takeshi; Yano, Koichiro; Ikari, Katsunori; Hiroshima, Ryo; Fukagawa, Shingo; Nasu, Yuki; Okazaki, Ken
Abstract: Objectives: To evaluate factors associated with low back pain (LBP) and effect on quality of life (QOL) using patient-reported outcome in patients with rheumatoid arthritis (RA). Methods: Overall, 414 patients with RA who answered the Japanese Orthopedic Association Back Pain Evaluation Questionnaire (JOABPEQ) were included in this study. LBP-positive was defined a visual analog scale (VAS) of LBP (LBP VAS) of ≥ 30 mm. Results: The rate of LBP-positive group was 24.9%. Body mass index (BMI) (odds ratio [OR]: 1.116), tender joint count (TJC) (OR: 1.598), global VAS (OR: 1.016), and Health Assessment Questionnaire Disability Index (HAQ-DI) (OR: 2.392) were found as significant LBP-associated factors. When adjusted for sex and van der Heijde-modified total Sharp score, BMI (OR: 1.120), TJC (OR: 1.619), global VAS (OR: 1.016), pain VAS (OR: 1.015), and HAQ-DI (OR: 2.312) were found to be the significant factors associated with LBP. Moreover, LBP VAS had relatively high correlations in all domains of the JOABPEQ scores (correlation coefficient: LBP, −0.601; lumbar function, −0.624; walking ability, −0.548; social life function, −0.479; and mental health, −0.463). Conclusions: This study investigated the effect of LBP in patients with RA. The results of this study indicate that LBP is associated with the physical function and QOL in patients with RA. We believe that our results will be useful for physical function and QOL assessments in patients with RA with LBP.